IMPLEMENTASI KEBIJAKAN BADAN USAHA MILIK DESA DI DESA TULE KECAMATAN MELONGUANE TIMUR KABUPATEN KEPULAUAN TALAUD - RAMPENGAN, JUAN ANTONIO; LENGKONG, FLORENCE DAICY; RARES, JOYCE JACINTA (JURNAL ADMINISTRASI PUBLIK, 2019)
Village-owned enterprise is economic institutions at the village level that aims to manage the potential of the village and the villagers prosper which is managed by the Government of the village together with the community. Formation of the Village-owned enterprises carried out based on the aspirations of the community and Government consultation village. The purpose of this research is to know the implementation policy of the village-owned enterprise in the village of Tule Subdistrict Melonguane Talaud Islands Regency East. This research uses qualitative research methods, descriptive. Data collection techniques used are observation, interview and data collection with the document. To see how the implementation of the policy of the village-owned enterprise in the village of Tule Subdistrict Melonguane Talaud Islands Regency East. Researchers using four indicators: communication, resources, disposition and bureaucratic structure. Based on the results of this study stated that the implementation of the policy of the village-owned enterprise in the village of Tule Subdistrict Melonguane Talaud Islands Regency East haven't run well due to a lack of good communication, resources that have not been adequate, the absence of a commitment from implementers to implement policies and organizational structures that are not regular. Thus it can be concluded that the implementation of the policy of the village-owned enterprise in the village of Tule Subdistrict Melonguane Talaud Islands Regency East hasn't been going well.Keywords: Policy Implementation, Business Entity, The Village.